Randomized Complete Block Design to identify the most Important Factors Affecting Traffic Accidents in Iraq (Journal of the College of Basic Education, 2025)
Traffic accidents in Iraq are considered one of the most dangerous phenomena because of the threat they cause to the lives of citizens, as well as causing significant human and material losses. Statistics indicate a significant increase in the number of traffic accidents in recent years. Therefore, traffic safety is an important requirement to preserve the lives of road users and mitigate the social and economic impacts and psychological consequences resulting from it. Therefore, work must be done to reduce its risks through the combined efforts of all concerned parties, including government, civil society, and drivers. For this purpose, the focus of this research will be on studying and diagnosing the most important factors that affect traffic accidents in the governorates of Iraq, where a completely randomized blocks design was used to study the effect of six factors (treatments) represented in the causes of traffic accidents (Type of road, Causes of accident, Accident time, Type of transport, Age groups, Causes of accidents) with blocks representing the Iraqi governorates (Nineveh, Kirkuk, Diala, Al-Anbar, Baghdad , Babylon, Karbala, Wasit, Salah Aldeen, Al-Najaf, Al-Qadysia, Al-Muthanna, Thi -Qar, Missan, Basrah) except for the Kurdistan region. The statistical program was used The ready (CoStat) in the analysis of the research data, where several conclusions were reached through the results of the ANOVA tables, the most important of which is the presence of significant differences for all the factors included in the research, meaning that these factors have a clear and effective impact and are considered important causes of traffic accidents in the Iraqi governorates. It was also concluded through the least significant difference (LSD) test that the most influential levels of the factors are highways, main roads, drivers, and others.